Paulo Freire's Educational Approach as a Model of Christian Education in Reducing Poverty in the Village of Tumbang Manyoi Gunung Mas, Central Kalimantan - Rivosa Santosa; Demsy Jura (International Journal of Science and Society, 2023)
Poverty is a common thing that can occur in every region, region, and even any country in this world. However, poverty is not to be enjoyed or inherited but must be fought for to be eradicated so that one gets freedom from the condition of poverty itself. Many factors cause a person to become poor, one of which is the inability of a person to regulate his mindset so that he is also unable to overcome poverty directly. The absence of proper education for the people has made them poor, and in the end, the right to welfare has become impossible. Education for the poor needs to be done because the understanding that poverty has oppressed humanity must be immediately addressed. The mindset that sees poverty as oppression and must be fought for is not born without being shaped and encouraged by the educational process. But education for the poor is not easy because the priority is the basic life needs. Paulo Freire's educational approach which emphasizes critical thinking and dialogue; is considered relevant to the condition of poverty in Indonesia. Freire supports the birth of a change in mindset to be free from poverty. From a Christian perspective, the church has a role in cultivating spirituality and caring for the poverty of the surrounding community. The church needs a model to carry out Christian Education for its citizens. Researchers see that the influence of Christian Education in the village of Tumbang Manyoi, Miri Manasa sub-district, Gunung Mas district, Central Kalimantan province is relevant for the application. This study uses a qualitative approach with ethnographic studies. The research produces a model of Christian Education based on contextual cognition which emphasizes the concept of knowledge, experience, and application so that it can be applied in the church to people who are shackled by poverty.